A narrative inquiry into the fostering of a teacher-principal's best-loved self in an online teacher community in China. Issue 3 (27th May 2019) - Li, Jing; Yang, Xiaohong; Craig, Cheryl J.
ABSTRACT: This study revolves around an organically lived online community of Chinese elementary teachers. The teachers shared their reflective journals and engaged in conversations with the facilitators and also with their peers. Following one participant's postings over a span of thirteen months helped the research team to narratively explore how the teacher, through reflections and interactions with his other fellow community members, refined his personal practical knowledge and cultivated his best-loved self as a teacher-principal in a rural school in China that lacked learning resources. Highlighted in the discussions are how the participant integrated his personal being with his professional being and eventually became the teacher he wanted to be. This research study adds to the literature about teachers as agents of change. This knowledge contribution, among others related to technology, shows how professional development and the development of teacher identity can be promoted in online teacher knowledge communities. Implications for teacher education are also discussed.